2008
DOI: 10.1148/radiol.2483071958
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Metastases: In Vivo Assessment of Perfusion Parameters at Dynamic Contrast-enhanced MR Imaging with Dual-Input Two-Compartment Tracer Kinetics Model

Abstract: This study was institutional review board approved, with waived patient consent for retrospective analysis of the data. The hepatic perfusion at dynamic contrast material-enhanced magnetic resonance (MR) imaging was commonly described and assessed by using a dual-input one-compartment tracer kinetics model. Although the tracer kinetics in normal liver parenchyma can be described by using a single compartment, functional changes in the tumor microenvironment can result in distinctly different tracer behavior th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 38 publications
7
90
0
Order By: Relevance
“…However, the approximation may not be true in the diseased liver owing to increased resistance to incoming sinusoidal blood flow caused by deposition of collagen or tumor cells in the space of Disse and altered sinusoidal architecture through the loss of fenestrae between sinusoidal endothelial cells (30). Therefore, most CT perfusion studies of the liver have used a dual-compartment model to better reflect the microcirculation of the diseased liver resulting from tumor or cirrhosis, although dual-compartment models are computationally more demanding (43). hepatic arterial and portal venous blood supply in normal liver tissue and liver lesions is important for characterization and treatment response evaluation of liver nodules (44)(45)(46).…”
Section: Calculation Of Ct Perfusion Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the approximation may not be true in the diseased liver owing to increased resistance to incoming sinusoidal blood flow caused by deposition of collagen or tumor cells in the space of Disse and altered sinusoidal architecture through the loss of fenestrae between sinusoidal endothelial cells (30). Therefore, most CT perfusion studies of the liver have used a dual-compartment model to better reflect the microcirculation of the diseased liver resulting from tumor or cirrhosis, although dual-compartment models are computationally more demanding (43). hepatic arterial and portal venous blood supply in normal liver tissue and liver lesions is important for characterization and treatment response evaluation of liver nodules (44)(45)(46).…”
Section: Calculation Of Ct Perfusion Parametersmentioning
confidence: 99%
“…To circumvent this problem, a single-input model for perfusion imaging of hepatic metastases has been proposed with the assumption that the vascular supply of liver metastases is predominantly arterial (Fig 4a). However, this assumption may not hold true for all histologic types of metastases as some liver metastases may have a mixed vascular supply (42,43). Ng et al (44) recently reported that a dual vascular input model (arterial and portal venous) for analysis of CT perfusion data sets improves test-retest reproducibility.…”
Section: Single-compartment Versus Dual-compartment Modelmentioning
confidence: 99%
“…However, the interstitial compartment (EES) may have a larger radial dimension (compared with its axial dimension) without a radial concentration gradient, and can be regarded as largely homogeneous. The impulse residue function for DP2 model can be given by two physiologic phases (63)(64)(65)(66)(67)(68)(69):…”
Section: Distributed Parameter (Dp) Models and Variationsmentioning
confidence: 99%
“…Also, by setting E or PS ¼ 0, the single-(vascular) compartment DP model, R DP1 (t), is simply given by R p (t). The physiological meaning of the two transport phases can be explained as follows (63)(64)(65)(66)(67)(68)(69). During the initial vascular transit phase 0<t<t p , R p (t) is a constant (unity) reflecting the fact that the total amount (100%) of tracer in the injected bolus is residing in the tissue, although a portion of the tracer could diffuse from the IVPS into EES.…”
Section: Distributed Parameter (Dp) Models and Variationsmentioning
confidence: 99%
“…It produces values for the blood (or plasma) flow, arterial blood flow fraction, extracellular volume, and mean transit time. In tumors, a dual-input two-compartment exchange model may be required to fit the data accurately, producing additional parameters: blood volume and interstitial volume, and permeability-surface area product [58]. When using Gadoxetic acid, a third intracellular compartment must be added to these models to characterize the intracellular phase of the tracer (Fig.…”
Section: Discussionmentioning
confidence: 99%